2022
DOI: 10.1111/jvh.13719
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards the elimination of hepatitis B in children in Colombia: A novel two‐phase study approach

Abstract: The World Health Organization (WHO) has established a target to eliminate mother‐to‐child‐transmission (EMTCT) of hepatitis B virus (HBV), defined as a prevalence of hepatitis B surface antigen (HBsAg) of ≤0.1% among children, by 2030. Using nationally representative serosurveys to verify achievement of this target requires large sample sizes and significant resources. We assessed the feasibility of a potentially more efficient two‐phase method to verify EMTCT of HBV in Colombia. In the first phase, we conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Most of the achievements in the reduction in hepatitis B incidence are due to the use of a highly effective vaccine early in childhood. In fact, some WHO regions, like Europe (EURO) and the Americas and the Caribbean (PAHO), have achieved the goals of eliminating mother-to-child transmission [ 17 ]. However, there are fewer advances for the treatment and cure of the people who were infected before the vaccine was available, which amounts to an estimate of 257 million people.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the achievements in the reduction in hepatitis B incidence are due to the use of a highly effective vaccine early in childhood. In fact, some WHO regions, like Europe (EURO) and the Americas and the Caribbean (PAHO), have achieved the goals of eliminating mother-to-child transmission [ 17 ]. However, there are fewer advances for the treatment and cure of the people who were infected before the vaccine was available, which amounts to an estimate of 257 million people.…”
Section: Discussionmentioning
confidence: 99%
“…There are substantial ongoing challenges in delivery, consistency and equity of supply, maintenance of the cold chain, timely administration (particularly to babies born outside healthcare settings, in indigenous communities and in rural areas), and political acceptance of the need for HepB-BD vaccination. 95 Despite global mandates, HepB-BD has not been consistently incorporated into regional or national guidance. In 2018, the coverage remained heterogeneous, globally estimated at 43%, and as low as 4-12% for the WHO Africa Region, where only 17/47 countries have formally adopted the strategy, compared to 75% in Latin America and >80% in the Western Pacific.…”
Section: Hepb-bd Vaccination: Challenges and Data Gapsmentioning
confidence: 99%
“…A recently leading-edge study demonstrated important advances in achieving the goal of hepatitis B elimination in Colombia [ 29 ]. The study evaluated the feasibility of a two-phase approach to verify mother-to-child transmission of HBV in this country.…”
Section: Epidemiology Of Hbv Infectionmentioning
confidence: 99%
“…A total of 3203 children from these municipalities were screened for HBV infection marker. HBsAg was not detected in any of the 3203 samples, yielding an upper 90% confidence limit of <0.1% prevalence [ 29 ]. Importantly, the study reported that there are still populations in which vaccination coverage is low, such as home-born children and indigenous communities.…”
Section: Epidemiology Of Hbv Infectionmentioning
confidence: 99%